Sharia Financial Literacy And Inclusion In Islamic Boarding Schools Of Rabithah Of Islamic Ma'ahid Of Nahdlatul Ulama DKI Jakarta - Nur Hidayah; Abdul Azis; Nadhil Novarel Mathari; Tira Mutiara (Universitas Islam Negeri Alauddin Makassar, 2023)
This study aims to determine the index of Islamic financial literacy and inclusion in Islamic boarding schools with a case study at RMI NU DKI Jakarta and analyze the effect of Islamic financial literacy and inclusion on welfare proxied by Maqashid Sharia. Primary data analyzed with descriptive statistics to measure the Islamic financial literacy and inclusion index; and SEM-PLS to analyze the effect of Islamic financial literacy and inclusion on welfare proxied by Maqashid Sharia. The results showed that 34% of respondents had Islamic financial literacy and inclusion index well-literate, 57% in sufficient literate, and 9% in less literate. Islamic financial literacy has a significant positive effect on welfare proxied by Maqashid Sharia. Meanwhile, Islamic financial inclusion has a positive but insignificant effect. The government and Islamic financial institutions must increase the socialization of Islamic financial literacy in Islamic boarding schools and increase access to finance by adequate supporting infrastructure.